Nuevas hipótesis sobre la historia del Códice Tudela o Códice del Museo de América - Batalla Rosado, Juan José (Revista Española de Antropología Americana, 2001)
In this paper we introduce new hypothesis about the history of the Codex Tudela. We expose the theory that Francisco Cervantes de Salazar could be the owner of this document in the sixteenth century, and Juan Bautista Muñoz in the eighteenth century. The codex was bought in La Coruña (Spain) in 1799. Finally, We will argue about two important facts related to the present history of the Codex